Induced sputum inflammatory measures correlate with disease severity in children with obstructive sleep apnoea. Issue 1 (23rd August 2006) - Li, A M; Hung, E; Tsang, T; Yin, J; So, H K; Wong, E; Fok, T F; Ng, P C
Abstract : Objective: To establish the association between airway inflammation and severity of obstructive sleep apnoea (OSA) in children. Methods: Consecutive children presenting with symptoms suggestive of OSA were recruited. They completed a sleep apnoea symptom questionnaire, underwent physical examination, spirometry, sputum induction and an overnight polysomnography. Adequate sputum contained <50% squamous epithelial cells, and OSA was diagnosed if the obstructive apnoea index was >1. Results: 73 children with a median (interquartile range (IQR)) age of 11.3 (10.0–13.2) years were recruited. There were 21 girls and the median body mass index of the group was 24.0 (18.0–27.0) kg/m 2 . The most common presenting symptoms were habitual snoring, mouth breathing and prone sleeping position. Sputum induction was successful in 43 (59%) children, of whom 14 were found to have OSA. Children with OSA had significantly greater percentage sputum neutrophil than those without OSA (18.5 (IQR 8.0–42.0) v 4 (IQR 3.0–11.3), p = 0.006). On multiple regression analysis, percentage sputum neutrophil was significantly associated with OSA (odds ratio = 1.1, p = 0.013). Conclusion: Children with OSA had airway inflammation characterised by a marked increase in neutrophils. Further studies are needed to confirm these findings and to better define the downstream cellular interactions and molecular pathogenesis in childhood OSA.